A choice experiment to estimate visitor preferences for ecotourism attributes at Kenyir Lake, Malaysia - W Mohamad, Wan Norhidayah (2013)
Kenyir Lake is one of the popular ecotourism destinations in Malaysia which offers spectacular scenic beauty to the visitors. Water transportation is the main method of travel here and the popular water transportation is the house boat service. Tourism industries at Kenyir Lake generate large financial income from house boat attractions,and therefore improvement of these services and the determination of relevant policies for management and maintenance are vital for future development. The objectives of this research are to evaluate the attitude and perception of the visitors towards the recreational aspects of Kenyir Lake and to evaluate the visitors’ preferences for house boat services attributes at Kenyir Lake. Data was obtained by using questionnaires as part of a face-to-face interview with the visitors who rented house boats during their vacation at Kenyir Lake. A total of 285 respondents were interviewed over January to March 2012. The results show that most of the visitors are satisfied with the ecotourism resources and services at Kenyir Lake. Many of them are first time visitors to the lake while the rest have visited more than once. The data was analysed by using descriptive analysis and the choice experiment method (CE). Descriptive analysis is used to analyse the socio-economic profile of the visitors and the attitude and perception of the visitors towards the ecotourism services at Kenyir Lake. The visitors’ preferences for house boat services were estimated by using a Choice Experiment. In the CE part, five categories of non-market values of house boat services were defined including: tourist guide, safety equipment, communication system, activity packages and extra package prices. The results demonstrated the respondents positive willingness to pay (WTP) for three attributes of house boat services, namely the tourist guide, safety equipment and premium package activities with averages of WTP of 8.98%, 23.85% and 26.8% respectively. These findings indicate that respondents are willing to pay for an improvement from the status quo to a better level of services. The findings of this study may guide and assist policy makers, authorities and local managers to better consider the consequences of maintaining the current condition of the services provided to the visitors.